Factores sociales que influyen en el comportamiento agresivo de los estudiantes entre 10 y 12 años matriculados en la institución educativa n| 81515 "miguel grau" casa grande - durante el año 2014 - Cáceda Fasshauer, Maria Pamela (2014)
This research report has been aimed at identifying and analyzing the consequences that generate social factors that influence aggressive behavior of students between 10 and 12 years enrolled in the Educational Institution No. 81515 "Miguel Grau" Casa Grande District. During the research was done using descriptive design; and to achieve research results, we worked with a total of 40 children, aged between 10 and 12 years. In Chapter I; gathering information from the study, which was essential to make a thorough review of various documentary sources is detailed; to understand the topic under study, the concepts that frame the subject and have a guide through various research work carried out in previous years. In turn, the background according to framing the issue, have been helpful to tell as the problem being affected humanity at local, national and international study. Likewise, there are various theories that support what you want to convey to the reader, so that it comes to solving the problem. And finally, with a conceptual framework that helps to define each of the terms used in the problem under study. In Chapter II, it was essential to make use of qualitative research techniques (such as observation and interview), and qualitative techniques (such as the questionnaire); such techniques and instruments were valuable to translate the information collected and contrast with the hypotheses. In Chapter III, the statistical method helped get clarity of reality in which the group is being studied, showing that aggressive behavior limits their level of personal development, and leads to be rebellious and irresponsible humans It is important and essential to establish that all behavior is influenced by a particular element, which is marked by the kind of culture that has the person as existing social norms in their environment or the attitude present at all times. Finally it is necessary to establish as a proposed change is effective liaison between parents and children, teaching children to solve problems that there are several alternatives, avoiding fights.